7 - Propos sur un « Bandoeng » épistémique : l’Afrique, le Sud global et la production des savoirs au XXIe siècle - Tshibambe, Germain Ngoie (Journal of Higher Education in Africa, 2022)
Knowledge production is among the pillars of globalisation. Through the lens of geopolitics it is worth understanding that knowledge production field is marked by the hegemony of few States and peoples, let us say the North. This hegemonic stand is kept thanks to diverse devices that are as such pitfalls and decoys aimed surreptiously at keeping the uneven balance within the act of thinking. Susan Strange displayed the game nations play in the field of power and she forged the “structural notion of power” (1988). Knowledge and knowledge circulation remain important as the vectors of the global hegemony. The global partition of knowledge production makes Africa lagging while being under strains of complex dependency. Africa’s posture is labelled “epistemic coloniality”. This article aims at analysing what Africa’s scholars are doing so as to free themselves at the epistemic level in the domain of social sciences. Following the paths of epistemic decoloniality we try to grasp what Africa is undertaking through the new spirit of Bandoeng at the epistemic front.